(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In recent years, researchers in various fields of medicine have been paying increased attention to the study of the state of cerebral hemodynamics, due to the increasing increase in morbidity and mortality from cerebrovascular disorders. MK is the most acceptable for studying the vegetative support of adaptation processes, since it is an independent functioning system, occupying an exceptional position among other organ vascular basins and possessing its own regulatory mechanisms. Reduced adaptation and compensatory capabilities of MC lead to hypoxia, cerebral dysfunction and the initial manifestations of cerebrovascular insufficiency, which is associated with a violation of autoregulatory mechanisms.